Malay vocabulary mastery of attention deficit hyperactivity disorder students - Abd. Nasir, Siti Noridayu; Abdul Halim, Hazlina; Kamaruddin, Rohaidah (Universiti Kebangsaan Malaysia, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is a problem of distraction, confusion and lack of focus in aspects of learning. It involves mastering the vocabulary of the ADHD student's first language. Therefore, this study was conducted to identify the mastery of Malay vocabulary through visuals about career and discuss the mastery of Malay vocabulary with Skinner's Theory of Behaviorism. The two objectives of this study are qualitatively discussed in depth. The respondent for this study is a 15-year-old ADHD male student. A total of 20 research items about the type of job that respondents need to answer using the correct Malay vocabulary. Items are given in the form of colored visuals and respondents only have to answer the type of job according to the displayed visuals. The findings of the study show that only eight questions can be answered correctly using the correct Malay vocabulary. So, there are 12 question items that fail to be answered correctly using the correct Malay vocabulary. This happens because ADHD students' mastery of Malay, which is not the same as normal students at the age of 15, has mastered more complex Malay vocabulary. Nevertheless, the influence of the use of English vocabulary as a second language can be controlled due to repeated use in the respondent's family environment. The application of Skinner's Behaviorime Theory in the application of positive reinforcement can motivate mastery for learning Malay vocabulary. However, negative reinforcement gives the effect of lack of confidence in the process of learning Malay vocabulary when reprimanded for giving incorrect answers. This study suggests that the families of ADHD students help improve the mastery of Malay vocabulary through oral, visual training and watching appropriate shows.